Genetic Analysis of Sugar Composition and Its Relationship with Protein, Oil, and Fiber in Soybean. Issue 6 (30th August 2018) - Jiang, Guo-Liang; Chen, Pengyin; Zhang, Jiaoping; Florez-Palacios, Liliana; Zeng, Ailan; Wang, Xianzhi; Bowen, Ronald A.; Miller, Amanda; Berry, Haley
Abstract : Soybean [ Glycine max (L.) Merr.] is one of the most important crops in the world. It is a major source of vegetable oil for consumption and protein meal for animal feeds and has also been widely used in human food industries because of its nutritive and health benefits. To provide useful information for soybean quality improvement, seed individual sugars, total sugar, protein, oil, and dietary fiber were genetically analyzed in replicated trials with 323 germplasm lines grown in South Dakota and 137 cultivars and breeding lines grown in Virginia. The results indicated significant differences among the genotypes for all traits investigated. Environment effect and genotype × environment interaction were also significant in most cases. Heritability estimates were high (94.45–97.79%) for all traits in the germplasm population, and higher in the population of breeding lines for most traits. High genotypic correlation existed between sucrose and total sugar, which helps improvement of digestible sugars and sweetness in soybean food. However, attention should be paid to the lines with higher sucrose but lower oligosaccharides, since stachyose was positively associated with total sugar. Genotypic correlations between seed sugars and protein were insignificant or very low in most cases, implying that alteration of seed sugars might not necessarily affect protein. In some cases, however, there might be negative correlations between seed sugars and oil or dietary fiber in soybean. This study also identified some unique germplasm lines with a desired level of a specific seed composition: one with high sucrose, five with low raffinose, 15 with high total sugar, seven with high protein, and four high in both sucrose and total sugar.